(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper delves into the intricate landscape of cryptocurrency investment behavior by focusing on individuals who possess awareness and engage in cryptocurrency investment. With the rapid proliferation of cryptocurrencies, understanding investor perceptions and preferences becomes crucial for both academia and the financial industry. The study’s objectives are twofold: firstly, to explore the relationship between investors’ risk perceptions and the extent of their cryptocurrency investments, and secondly, to examine how perceived benefits of diversification impact the inclination to include cryptocurrencies in investment portfolios. A quantitative approach is adopted, collecting data from 400 participants in Pune, India, who are cryptocurrency-aware investors. The findings reveal a strong positive correlation between risk perception and the extent of cryptocurrency investment, indicating that individuals with higher risk perceptions tend to invest more significantly in cryptocurrencies. Moreover, the study establishes a significant influence of perceived benefits of diversification on the preference for cryptocurrency inclusion in investment portfolios, underscoring the role of diversification as a motivational factor. These outcomes contribute to a deeper comprehension of cryptocurrency investment behavior and its interplay with risk perception and diversification preferences.